The Influence of Entrepreneurship Motivation and Self Efficacy on Agribusiness Students’ Entrepreneurial Intention - Ranjiv A.A Sihombing; Nur Baladina; Mofit Jamroni; Anisa Aprilia; Novi Haryati (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
The growing number of university graduates in Malang, Indonesia, is not matched by the availability of formal job opportunities, encouraging many individuals to pursue entrepreneurship as a feasible career choice. Within the agribusiness sector, this opportunity remains largely untapped despite the abundance of local resources and market opportunities. The objective of this research is to examine how entrepreneurship motivation and self-efficacy affect the intention to become entrepreneurs among Agribusiness students at Brawijaya University. The research was conducted between October and December 2024 using a quantitative approach. Data were obtained from 80 active students with entrepreneurial experience using a structured questionnaire based on a Likert scale. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results reveal that both entrepreneurship motivation and self-efficacy have a significant and positive influence on entrepreneurial intention, with an R-squared value of 0.637. This implies that 63.7% of the variance in entrepreneurial intention is explained by the two independent variables. The most influential factor within entrepreneurship motivation is the influence of social conditions, while the strongest indicator of self efficacy is the belief in achieving business goals. These results suggest that a combination of strong internal drive and self-confidence is essential in fostering entrepreneurial behavior among students. The implication of this study is the need for universities to strengthen entrepreneurship programs by integrating real-world experiences, mentoring, and exposure to successful role models in agribusiness. Enhancing these elements may better prepare students to become innovative entrepreneurs who contribute to sustainable economic development.